(untitled) (Research, Society and Development, 2020)
Hypertension is a multifactorial condition with high rates of complications such as cardiovascular and renal diseases, making it a worldwide public health concern. This disease alters calcium regulation by inducing bone loss, which is limited by anti-hypertensive drugs. One such drug, losartan, inhibits angiotensin II (Ang II) AT1 receptors. The aim of this study was to compare the process of alveolar repair in spontaneously hypertensive rats (SHR) and Wistar rats, and to assess the effect of losartan on bone dynamics. Treated and untreated rats underwent dental extraction of the upper right incisor and were euthanized 7, 14, or 28 days after surgery. Alveolar repair was then analyzed histomorphometrically and immunohistochemically by measuring proteins involved in bone metabolism. Data were analyzed using the nonparametric Kruskal-Wallis test, followed by the Mann Whitney test for comparison of samples at different times. Alveolar repair was slow in SHRs, while losartan increased bone formation and trabecular thickness in both SHRs and Wistars. Because the analyzed proteins are found in dynamic bone, it is suggested that losartan interferes with the actions of angiotensin II and the renin-angiotensin system and limits bone metabolism.